Planning for Diversity Options and Recommendations for DoD Leaders - Lim, Nelson (RAND Corporation, 2008)
Discusses initial steps that the Department of Defense (DoD) should take in developing a department-wide strategic plan to achieve greater diversity within its active duty and civilian leadership. Key questions include how diversity will be defined, how progress toward diversity will be measured, and how DoD leaders will hold themselves and others accountable for such progress. Includes a summary of findings from the 2007 DoD Diversity Summit.